The Long Run Economic Effects of Medical Innovation and the Role of Opportunities - Sonia R. Bhalotra; Damian Clarke; Atheendar Venkataramani (Institute of Labor Economics (IZA), 2025)
We leverage the introduction of the first antibiotic therapies in 1937 to examine the long-run effects of early-childhood pneumonia on adult educational attainment, employment, income, and work-related disability. Using census data, we document large average gains on all outcomes, alongside substantial heterogeneity by race and gender. On average, Black men exhibit smaller schooling gains than white men but larger employment and earnings gains. Among Black men (and women), we identify a pronounced gradient in gains linked to systemic racial discrimination in the pre–Civil Rights era: individuals born in more discriminatory Jim Crow states realized much smaller gains than those born in less discriminatory states. There is no similar gradient among white Americans. Women of both races exhibit smaller education and earnings gains than men on average, consistent with cultural and institutional barriers to women's work. Our findings highlight the role of opportunities in shaping the extent to which investments in early-life health translate into longer run economic gains.
Keywords: I10; I14; J71; H70; 330; early childhood; medical innovation; race; human capital production; education; income; disability; systemic discrimination; institutions; infectious disease; pneumonia; antibiotics; sulfa drugs